2018
DOI: 10.1038/s41598-018-22531-2
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and interpretation of deleterious coding variants in terms of protein structural stability

Abstract: The classification of human genetic variants into deleterious and neutral is a challenging issue, whose complexity is rooted in the large variety of biophysical mechanisms that can be responsible for disease conditions. For non-synonymous mutations in structured proteins, one of these is the protein stability change, which can lead to loss of protein structure or function. We developed a stability-driven knowledge-based classifier that uses protein structure, artificial neural networks and solvent accessibilit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 46 publications
0
60
0
Order By: Relevance
“…In recent years, several studies-some accompanied by publicly accessible tools-have supported the idea that structural data, in addition to classical conservation analyses based on multiple sequence alignments (MSAs), provide a means to predict the effect of single amino acid substitutions on biological function [17][18][19][20]. We recently showed that a consideration of not only structure but also structural dynamics can further improve the accuracy of these predictions [21].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several studies-some accompanied by publicly accessible tools-have supported the idea that structural data, in addition to classical conservation analyses based on multiple sequence alignments (MSAs), provide a means to predict the effect of single amino acid substitutions on biological function [17][18][19][20]. We recently showed that a consideration of not only structure but also structural dynamics can further improve the accuracy of these predictions [21].…”
Section: Introductionmentioning
confidence: 99%
“…SNPMusic, the stability-oriented knowledge-based classifier, uses protein structure, artificial neural networks, and combinations of solventdependent statistical potentials to predict whether destabilizing or stabilizing mutations cause disease (Ancien, Pucci, Godfroid, & Rooman, 2018).…”
Section: Structure-based Methodsmentioning
confidence: 99%
“…The main purpose of this study was to analyze the protein structural and functional impact of the sequence variants in the HBA1 , HBA2 , and HBB genes reported in the gnomAD database, and to improve the description of the observed clinical outcomes. Although there are many computational and bioinformatic methods available for predicting a possible pathogenic effect of an amino acid substitution (Ancien, Pucci, Godfroid, & Rooman, ; Mahmood et al, ), none of these consider the different phenotypes that can result as a consequence of these variations. Moreover, the differential impact of these changes in the different conformations of a protein should be considered (Juritz et al, ) and many current methods usually analyze only one structure per protein.…”
Section: Introductionmentioning
confidence: 99%